18 F-FDG PET/CT imaging of a Grade 3 lymphomatoid granulomatosis in an immunocompromised pediatric patient - KESİM, SELİN; ÖZGÜVEN, SALİH; ÖNEŞ, TUNÇ (My University, 2023)
Lymphomatoid granulomatosis is a rare extranodal Epstein-Barr virus-driven B-cell lymphoproliferative disease, involving predominantly lung, less often skin, kidney, and central nervous system. Here, we present a pediatric case with primary immunodeficiency, diagnosed with pathologically proven pulmonary grade-III lymphomatoid granulomatosis.18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) imaging demonstrated18F-FDG avid pulmonary masses with central air-bronchograms and cavitations. Although the definitive diagnosis depends on biopsy,18F-FDG PET/CT serves as a complementary imaging tool to evaluate the extent of the disease and response to treatment.
Primer immün yetmezliği olan evre 3 lenfomatoid granülomatozis tanılı pediatrik bir hastanın18F-FDG PET/BT görüntülemesi
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; 18F-FDG PET/CT; Lymphomatoid granulomatosis; pulmonary involvement